Modular Prefabrication and Accounting Transaction for Internal Control: A Modular-Lean-Control Integration Model - Noor Prihartanto; Bambang Endro Yuwono (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Conventional projects struggle with complex accounting, weak controls, and fragmented payments that hinder administration and reporting, whereas modular prefabrication simplifies production and transaction processes. This study examines the influence of modular prefabrication on the simplification of accounting transactions and strengthening the internal control of the project, as well as formulating an applicable modular-lean-control integration model. The study employed a qualitative-quantitative case study on a prefabricated modular project, using interviews, project documents, and financial records, with value stream mapping, risk-control matrix, and pre-post quantitative comparisons for analysis. The results showed a decrease in transaction points from ±120 points to ±48 points (a decrease of around 60%), an acceleration of payment verification time from ±14 days to ±4 days (acceleration up to 70%), a reduction in administrative costs by 40-50%, and an increase in financial reporting accuracy of up to ±98%. These findings indicate that the integration of modular prefabrication with lean construction principles and based internal control can result in more effective control structures through module batch mechanisms and physical-cost verification gates. This research contributes to the development of integrative conceptual models that are relevant to industrial practice and academic research.